Understanding and Managing Urban Water in Transition - Grafton, Quentin; Daniell, Katherine A.; Nauges, Céline; Rinaudo, Jean-Daniel; Chan, Noel Wai Wah (Global Issues in Water Policy, 2015)
This book examines changes and transitions in the way water is managed in urban environments. This book originated from a joint French-Australian initiative on water and land management held in Montpellier, France. The book delivers practical insights into urban water management. It links scientific insights of researchers with the practical experiences of urban water practitioners to understand and respond to key trends in how urban water is supplied, treated and consumed. The 51 contributors to the volume provide a range of insights, case studies, summaries and analyses of urban water and from a global perspective. The first section on water supply and sanitation includes case studies from Zimbabwe, France and South Africa, among others. Water demand and water economics are addressed in the second section of the book, with chapters on long-term water demand forecasting, the social determinants of water consumption in Australian cities, a study of water quality and consumption in France, governance and regulation of the urban water sector and more. The third section explores water governance and integrated management, with chapters on water management in Quebec, in the Rotterdam-Rijnmond urban area, in Singapore and in Australia. The final section offers perspectives on challenges and future uncertainties for urban water systems in transition. Collectively, the diverse insights provide an important step forward in response to the challenges of sustainably delivering water safely, efficiently and equitably.